2010
DOI: 10.1007/s10439-010-9934-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Time Effects of Dextran Exposure on Endothelial Cell Viability, Attachment, and Inflammatory Marker Expression In Vitro

Abstract: Dextran is commonly used to alter growth medium rheological properties for in vitro flow experiments in order to match physiological parameters. Despite its acceptance in literature, few studies have examined dextran effects on cells. In this study, we investigated changes in endothelial cell function due to dextran, under static and flow conditions, in a concentration and time-dependent manner. Dextran increased endothelial cell viability, decreased their ability to attach to culture plates and decreased leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
2
20
2
Order By: Relevance
“…Dex has excellent biocompatibility, and has been used in clinics for a long time, but modification of cell-cell interaction and cell viability has also been observed. 31 However, our data found no impact on viability and autophagy of cells by Dex. These results indicated that these NPs had good biocompatibility.…”
Section: Discussioncontrasting
confidence: 71%
“…Dex has excellent biocompatibility, and has been used in clinics for a long time, but modification of cell-cell interaction and cell viability has also been observed. 31 However, our data found no impact on viability and autophagy of cells by Dex. These results indicated that these NPs had good biocompatibility.…”
Section: Discussioncontrasting
confidence: 71%
“…The calibrated spacers used as cone supports provided a simple and accurate method for positioning the cone and modulating the gap h 0 between the cone apex and the plate surface. The addition of high molecular weight dextran to cell culture medium, allows us to investigate a wide range of WSS magnitudes ensuring the onset of primary, laminar flow without compromising cell biology (Rouleau et al 2010). Even at the highest cone rotation velocity, limited to 20 rad/s for safety reasons, the modified Reynolds number remains lower than 0.5, and thus negligible secondary flows develop (Sdougos et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…1. The viscosity of the cell culture medium was measured to be 0.975 cP at 37°C using a double gap rheometer (Bohlin, Model CVO 120 h) (Rouleau et al 2010b). From the measured viscosity and model radius, the following equation was used to calculate the volumetric flow rate (Q) required to obtain a desired wall shear stress in a straight rigid tube.…”
Section: Flow Experimentsmentioning
confidence: 99%